Hidden versus revealed attitudes: A list experiment on support for minorities in Ireland - McGinnity, Frances; Creighton, Matthew; Fahey, Éamonn (ESRI and Irish Human Rights and Equality Commission (IHREC), 2020)
New research published today reveals the gap between what people say in public about their attitudes to minorities in Ireland, and what they say when afforded anonymity. The study challenges previous assumptions about people’s views, and has implications for policy approaches to foster interculturalism.